Prevalence and risk factors associated with metabolic syndrome among university students in Bintulu, Sarawak, Malaysia - Mahmud, Sharifa Sadia; Robin, Tunung; Sarbini, Shahrul Razid (Universiti Putra Malaysia, 2023)
Introduction: Metabolic syndrome has become a worry for health of youth in Malaysia. This study aimed to look at the prevalence of metabolic syndrome, and to assess the risk factors of metabolic syndrome among Malaysian university students. Methods: A cross-sectional study was conducted on 248 students aged 18-30 years using a random sampling method from two universities in Bintulu, Sarawak, Malaysia. Data on sociodemographic, dietary habits and lifestyle were collected by a pre-tested self-reported questionnaire. Biochemical measurements, blood pressure, and anthropometric measurements were measured by standard procedures. Metabolic syndrome was defined according to Harmonized Joint Interim Statement criteria. Data were analysed using IBM SPSS 23.0 version. Results: The overall prevalence of metabolic syndrome was 12.5% and was more prevalent in male (17.5%). Indian (15.8%) was the most prevalent ethnic group, while Chinese (4.9%) had the least prevalence. 31.5% respondents had at least one metabolic component. Low HDL (42.7%) and large waist circumference (26.2%) were the most common components. Statistically significant (p<0.05) independent factors for developing metabolic syndrome were male, staying time more than six hours on computer/TV/mobile phone, in smokers, taking meals more than three times per day, and high consumption of soft drinks. Besides that, with high consumption of vegetables, the prevalence of metabolic syndrome was significantly low (p<0.05). Conclusion: These study findings elicit the evidence of increasing tendency and warning on metabolic syndrome for Malaysian university students, and considerable association of the prevalence of metabolic syndrome to dietary habits and lifestyle.